New GATE Digitizer Unit for versions post v9.3 - Kochebina, Olga; Bonifacio, Daniel A. B.; Konstantinou, Georgios; Paillet, Adrien; Pommranz, Christian M.; Razdevšek, Gašper; Sharyy, Viatcheslav; Yvon, Dominique; Jan, Sebastien (Frontiers in Physics, 2024)
The Digitizer Unit plays an important role for modeling with GATE, GEANT4 based platform for numerical simulations in medical imaging and radiotherapy. It simulates the response of the photodetection components by a sequence of analytical and semi-analytical models. The Digitizer Unit was written for the first versions of GATE, about 20 years ago. Since then it has in parts grown in a code that can be hardly maintained. Some parts of the code were unused or duplicated, some of the functionalities were non-working anymore. Therefore, the GATE Digitizer Unit update is required in order to incorporate the novelties of GEANT4, to clean up its current version and add new features. In this article, the new GATE Digitizer Unit implementation (since version 9.3) is presented. Added functionalities, the impact of changes on users, the current status of the work and perspectives are discussed.